CLINICAL AND LABORATORY CHARACTERISTICS AND TREATMENT OUTCOMES OF CYTOMEGALOVIRUS-ASSOCIATED THROMBOCYTOPENIA AT THE NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and laboratory characteristics and the treatment outcomes of patients with cytomegalovirus associated thrombocytopenia at the Clinical Hematology Department - National Children’s Hospital.Subjects: Seventy-six patients under 18 years old diagnosed with CMV-associated thrombocytopenia and treated at the Clinical Hematology Department - National Children’s Hospital, of whom treatment outcomes were evaluated in 74 patients who were followed up during treatment.Methods: Descriptive case series.Results: CMV associated thrombocytopenia in this study was mostly observed in children under 12 months of age, accounting for 80.3%. Males were more common than females. The most common symptom was bleeding (100%), anemia (53.9%). Other symptoms were also recorded such as diarrhea (30.3%) and respiratory tract infection (22.3%). Most patients had severe thrombocytopenia
Keywords: xuất huyết giảm tiểu cầu, Cytomegalovirus, huyết học, Bệnh viện Nhi Trung ương.